The psychological typhoon eye effect in responses to terrorism. (2020) - Li, Shu; Li, Jiang-Long; Yang, Shu-Wen; Wu, Xiao-Ju; Chen, Jun-Fang; Ding, Yang; Lin, Yu-Xin; Bai, Xin-Wen; Luan, Sheng-Hua; Zheng, Rui
Terrorist attacks can occur anywhere. As the threat of terrorism develops, the China-Eurasia Expo held in Ürümqi, China is attracting fewer potential visitors. A nationwide survey of 2034 residents from 31 provinces and municipalities in China was conducted to examine the relation between the distance to respondents' city of residence from Ürümqi and their levels of concern for safety and security concerning the Expo. The two were found to be positively related: the closer the respondents lived to Ürümqi, the less concerned they were with the safety and security of the Expo. This is consistent with the "psychological typhoon eye" effect, which states that people living closer to the center of an unfortunate event (whether natural or man-made hazards) are less concerned with the event's negative consequences. This effect appears to hold for terrorism. There are implications of this finding for international counter-terrorism practice, tourism, and research.